Perceptions of the effectiveness of corporate sponsorship of the performing arts in South Africa - Berning, Paul H. (My University, 2011)
The Purpose of this research was to identify aspects of alignment between Absa, a sponsor of theatre in South Africa, and Packed House Productions, the producer and rights holder of theatre products sponsored by Absa, in terms of criteria that were identified as possible requirements for sponsorship effectiveness, and to measure the impact of sponsorship on consumer perceptions in terms of those criteria. During the course of the research four main criteria arose as strong common themes in the literature and were established as requirements to be met to ensure sponsorship effectiveness, they being: sponsorship objectives, communication presence, leveraging the opportunity and return on investment. A mixed method approach was utilised: Qualitative interviews were directed towards determining aspects of alignment between Absa and Packed House Productions with the criteria, and a quantitative survey using a questionnaire with answers based on a seven point Likert scale was directed towards determining the impact of sponsorship on the theatre consumer. The study concluded that Absa and Packed House Productions are almost completely aligned in their recognition of the importance of the criteria required for effective sponsorship. Two of the criteria were being met in full: sponsorship objectives and communication presence, it was found, however, that Absa did not leverage the sponsorship opportunity and that no effective tools were shown to be used to adequately determine return on investment. The third and fourth criteria were therefore not being met. The study revealed that the impact of sponsorship on the theatre consumer has been largely successful in terms of increased brand awareness and the generation of goodwill in the mind of the consumer towards Absa as an organisation. It was recommended that a greater focus on leveraging the sponsorship opportunity and the establishment of appropriate tools to measure sponsorship return on investment could increase sponsorship effectiveness.
MBA - WBS
Keywords: Corporate sponsorship; Performing arts